A Review of Baclofen Overdoses in Australia: Calls to a Poisons Information Centre and a Case Series. (1st December 2018) - Jamshidi, Nazila; Morley, Kirsten C; Cairns, Rose; Dawson, Andrew; Haber, Paul S
Abstract : PBS data demonstrates baclofen use is increasing in Australia, while calls to NSWPIC illustrate an increase in number of exposures associated with toxicity. Baclofen toxicity may require prolonged intensive care admission. To minimize harms associated, especially with off-label baclofen prescribing for AUD, prescribers should pay careful attention to psychiatric comorbidities, and closely monitor treatment and dispensing. Abstract: Aim: to describe trends in baclofen reports to Australia's largest Poisons Information Centre (PIC) and present a case series detailing severity of overdoses. Short summary: PBS data demonstrates baclofen use is increasing in Australia, while calls to NSWPIC illustrate an increase in number of exposures associated with toxicity. Baclofen toxicity may require prolonged intensive care admission. To minimize harms associated, especially with off-label baclofen prescribing for AUD, prescribers should pay careful attention to psychiatric comorbidities, and closely monitor treatment and dispensing. Methods: this is a retrospective observational study of baclofen overdoses reported to New South Wales PIC (NSWPIC) from January 1 2004 to 31 December 2016. In addition, referrals to a metropolitan toxicology service relating to baclofen toxicity from 2014 to 2017 were analysed. The number of Pharmaceutical Benefit Scheme (PBS) claims for baclofen were also reviewed. Results: during the 13-year study period, 403 cases of baclofen toxicity were reported to NSWPIC. There was a 230% increase in annual exposures over this period, 71% of patients were symptomatic, with 77% requiring hospitalization. Coingestants were reported in 53%, with 57% being psychoactive medications (including alcohol). An increase in number of baclofen dispensing episodes was also noted. From the five cases of deliberate self-harm reported to the metropolitan toxicology service, three obtained baclofen for management of alcohol use disorder (AUD) and required prolonged treatment in the intensive care unit (ICU). Conclusions: NSWPIC data shows an increase in number of calls regarding intentional baclofen exposures in parallel with increase the number of baclofen PBS claims. These closely parallel the increase in dispensing of baclofen since 2008. Case studies presented reinforce the severity of baclofen toxicity. Together, they demonstrate the potential risk of harm of baclofen prescribing, and the greater need for caution. Baclofen should be considered carefully in patients high risk of overdose or be used only in specialist services with close monitoring.